The effect of acquisitions on the performance of Nordic initial public offerings - Takala, Joel (My University, 2021)
Initial public offerings (IPOs) are an increasingly more popular way to gain capital for private companies. Standard academic theory suggests that companies go public to lower their cost of capital, to climb the pecking order or for strategic reasons. In the empirical literature these the- oretical predictions are not found. Literature finds companies to go public to make acquisitions. When the company goes public, they are infused with cash and the uncertainty around their valuation is removed. This leads to acquisitions by newly listed companies. Initial public offerings are a widely studied subject. The negative stock performance of the companies going public in the long run is named as the IPO anomaly. This thesis studies the IPO long-term performance in the Nordic countries and considers the effect of acquisitions on the stock returns. The sample consists of 201 Nordic IPOs from 2001 to 2016. These returns for these IPOs are benchmarked against a market index and style matching companies. The buy-and-hold return methodology is used to analyze the returns. To further confirm the findings calendar time re- gressions are used. The Fama and French three factor model is regressed on the calendar time portfolio of IPOs. This thesis finds IPOs to outperform the market index clearly. They do not however outperform their style matches. This is explained with the outperformance of smaller growth stocks in recent years as IPOs are smaller stocks with lower book-to-market. When con- trolled for style, the outperformance of IPOs disappears. Acquisitions during the first year of the company going public are on average value destroying. First-year acquirers underperform when controlled for style while non-acquirers overperform. When the acquisition period is extended to three years, acquirers overperform significantly and companies not making acquisitions un- derperform. First year acquirers’ managements might suffer from empire building or entrench- ment and rush to make acquisitions which are value destroying. If investors invest in IPOs making acquisitions after one year of being public, there are significant abnormal returns available. These abnormal returns also appear ex-post the acquisition period.

Listautumisannit ovat yhä suositumpi tapa yksityisille yrityksille pääoman keräämistä varten. Akateemiset teoriat toteavat yhtiöiden listautuvan laskeakseen heidän pääoman kustannustaan, saaden pääsyn pääomarahoitukseen tai strategisista syistä. Empiirisessä kirjallisuudessa näille teoreettisille syille ei löydetä todisteita. Kirjallisuus löytää yritysten listautuvan, jotta he voivat tehdä yrityskauppoja. Kun yritys listautuu pörssiin, se kerää uutta pääomaa ja epävarmuus yri- tyksen arvosta poistuu. Tämä johtaa listautuneiden yhtiöiden yrityskauppoihin. Listautumisannit ovat laajalti tutkittu ala. Listautuneiden yhtiöiden negatiivisia tuottoja pitkällä aikavälillä kutsu- taan listautumisanomaliaksi. Tämä pro gradu tutkii listautumisantien osaketuottoja pitkällä aikavälillä pohjoismaissa ja keskit- tyy yrityskauppojen vaikutukseen listautumisten tuotoissa. Otos koostuu 201 pohjoismaisesta listautumisannista vuosilta 2001 vuoteen 2016 asti. Otoksen yhtiöiden tuottoja verrataan mark- kinaindeksiin, sekä ominaisuuksiltaan samanlaisiin yhtiöihin. Tuottojen analysointiin käytetään osta ja pidä metodia. Vahvistaakseen tuloksia analysoidaan myös listautumisista muodostettujen kalenteri portfolioiden tuottoja. Fama ja French kolmen faktorin mallia käytetään kalenteri reg- ressiossa riippumattomina muuttujina ja riippuvana muuttujana toimii listautumisista muodos- tettu kalenteri portfolio. Tutkimuksessa havaitaan listautumisantien tarjoavan ylituottoa markki- naindeksiin verrattuna. Ylituotto kuitenkin katoaa, kun listautumisanteja verrataan ominaisuuk- siltaan vastaaviin yhtiöihin. Tätä selittää pienempien kasvuyhtiöiden vahvat tuotot viime vuosina. Listautumisannit ovat keskimäärin pienempiä yhtiöitä, joiden B/M-arvo on matalampi. Kun huo- mioidaan yhtiöiden ominaisuudet, listautumisten ylituotot katoavat. Ensimmäisenä vuonna lis- tautumisen jälkeen tehdyt yrityskaupat ovat keskimäärin arvoa tuhoavia. Ensimmäisenä vuonna yrityskauppoja tekevät häviävät verrokeilleen, kun listautumiset, jotka eivät tee yrityskauppoja voittavat ne. Kun yrityskauppojen tarkasteluperiodi pidennetään kolmeen vuoteen, yrityskaup- poja tekevien osakkeiden tuotto on selvästi korkeampi kuin listautujien, jotka eivät osta muita yhtiöitä.
Keywords: listing (stock market); acquisition; mergers; corporate acquisitions; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance